Successful resection after first‐line lenvatinib therapy in an advanced thymic carcinoma - Masatoshi Shimura; Kentaro Miura; Tomonobu Koizumi; Shintaro Kanda; Shuji Mishima; Daisuke Hara; Shunichiro Matsuoka; Takashi Eguchi; Kazutoshi Hamanaka; Takeshi Uehara; Kimihiro Shimizu (Thoracic Cancer, 2023)
Abstract Thymic carcinoma is a highly malignant tumor and treatment options are limited. Lenvatinib, a novel multitargeted kinase inhibitor, has recently been approved for the treatment of unresectable thymic carcinoma. There are no reports of complete surgical resection after the administration of first‐line lenvatinib in advanced thymic carcinoma. A 50‐year‐old man visited our hospital because a computed tomography (CT) scan of the chest showed a large thymic squamous cell carcinoma. We suspected malignant pericardial effusion, invasion of the left upper lobe of the lung, and left mediastinal lymph node metastases. The patient was diagnosed with WHO classification stage IVb disease. Lenvatinib therapy was started at 24 mg/day as first‐line therapy. Gradual dose reduction to 16 mg/day was required because of hypertension, diarrhea, and palmar‐plantar erythrodysesthesia syndrome as side effects. Chest CT findings after 6 months of lenvatinib therapy showed reduction of the main tumor, disappearance of the mediastinal lymph node metastases, and pericardial effusion. Complete salvage resection was successfully performed a month after discontinuation of lenvatinib. The patient has been disease‐free for 1 year without adjuvant therapy. Lenvatinib therapy is one of the promising therapeutic options for thymic carcinoma and may make salvage surgery increasingly useful for advanced thymic carcinoma.